Neurath and Van Eesteren: Facing the challenge of unifying the language of modern urbanism (ARQUISUR Revista, 2012)
We analyze the relationship between Neurath and the IV CIAM, about the attempts to unify the language of urban planning. We compare the Neurath's method of pictorial statistics with the criteria of urban representation supported by Van Eesteren. We evaluate the merits of both proposals and try to show that the differences concerning representation methods refer to a wider field of philosophical and ideological disagreements.
Keywords: IV CIAM; internationalization; pictorial statistics; topographic representation; urban planning